Shadow of the almighty the life and testament of Jim Elliot - Elliot, Elisabeth, 1927- (London, UK Hodder and Stoughton, 1959)
Includes photographs.
Jim and Elisabeth Elliot, Ed and Marilou McCully and Pete and Olive Fleming came from a Brethren background and established an assembly at Shandia. Jim, Ed and Pete, along with Nate Saint and Roger Youderian were martyred in Ecuador on January 8, 1956 and are known as the Auca five. If found change call# to 266/.9286/ELL and place in Archives
Keywords: Elliot, Philip James, -- 1927-1956; Brethren movement -- Missionaries -- Ecuador -- biography; Auca five